PHYSICAL PROPERTIES, FIBRE DIMENSIONS AND PROXIMATE CHEMICAL ANSLYSIS OF MALAYSIAN RATTANS - Mohd. Ali, Razak; Mohmod, Latif; K.C., Khoo; Kasim, Jamaludin (วารสารวนศาสตร์ไทย, 2022)
The physical properties, fibre morphology and chemical constituents of five Malasian canes, viz. Calamus manan (rotan manau), C. palustris var. malaccensis (rotan manau langkawi), C. scipionum (rotan semambu), Korthalsia rigida (rotan dahan) and Plectomiopsis griffithii (rotan mantang gajah), are reported. There is a wide variation in the fibre diamensions as well the physical properties of all the species studied. The fibres are relatively short (1.34 - 2.17 mm) and thick-walled. The oven-dry density ranges between 0.33 and 0.61 gcm-3 and tends to decrease form the basal towards the top portion. With the exception of the holocellulose contents, the chemical constituents differs the significantly in content with species and height. The higher contents of water and alkali solubles of the rattan observed in the study indicate that proper selection, preparation and treatment should be considered in order to prolong their service lives.